PENGARUH MOTIVASI, KEPEMIMPINAN, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN - Leo Agung Andaru; Wahyu Hidayat; Reni Shinta Dewi (Universitas Diponegoro, 2015)
Some of the factors that affect the performance of the employees include motivation, leadership, and work environment. This study aims to identify and explain the influence of motivation, leadership, and work environment on employee performance of operational Boshe VVIP Club Bali. This type of research is explanatory research. The technique of collecting data using interviews, documentation, observations, and questionnaires. The conclusion of this study is a significant difference between motivation, leadership, and work environment on employee performance of operational Boshe VVIP Club Bali Based on these conclusions, the company needs to pay attention to things about the chance of getting a reward for employees, the level of satisfaction of the employee benefits obtained , leadership skills and managerial skills for leadership, and are also more selective in the choice and placement of employees in accordance with the atmosphere of the working environment in Boshe VVIP Club BaliKeywords: compensation, work discipline, motivation to work, employee performance